Evidence-based practices for children with autism spectrum disorder - Reichow, Brian (Henry Stewart Talks, 2020)
Introduction to how evidence-based practice is being defined, The application of evidence-based practice for the treatment of children with autism spectrum disorders, Comprehensive treatment programs for children with autism spectrum disorders that have been shown to be evidence-based, Focal treatments for children with autism that have been shown to be evidence-based, Conclusions and future directions, Additional readings, resources, and references